CLÁUDIO OU A DIALÉTICA DO BUCOLISMO - Sarmatz, Leandro (Organon, 2012)
This is a reading on Cláudio Manuel da Costa’s sonnets which aims atdetecting tensions between culture and rusticity, tradition and lack of history. It intendsto unfold the idea of a “Brazilian bucolic” - retake of the historical patrimonyto trace the limits of the New World tradition - the interior of Cláudio Manoel daCosta´s poetry.